The Impact of Age on Perioperative Complications after Extremity Reconstruction with the Free Gracilis Flap: A Retrospective Cohort Study Involving 153 Patients - Weitgasser, Laurenz; Amr, Amro; Hladik, Michaela; Wechselberger, Gottfried; Daigeler, Adrien; Schoeller, Thomas; Medved, Fabian (Journal of Reconstructive Microsurgery, 2019)
Background The need for plastic and reconstructive surgery on elderly patients has been on the rise due to an increase in life expectancy in the past decades. Therefore, a study was conducted on young and elderly patients following microsurgical extremity reconstructions with free gracilis muscle flaps with the primary aim to investigate the influence of age and the American Society of Anesthesiologists (ASA) score on the general outcome, as well as surgical and medical complications.Methods A retrospective analysis of 153 patients receiving free gracilis muscle flaps for extremity reconstructions between November 2009 and January 2018 was performed at two partner institutions specialized in microsurgical reconstructions. A logistic regression analysis was performed to correlate age and the ASA score with postoperative complication probability. Patients younger than 70 years were directly compared with elderly patients with respect to age, gender, ASA score, preexisting comorbidities, localization, and postoperative medical and surgical complications.Results Age turned out to be not significantly associated with major flap complications (p = 0.925) but with higher ASA scores (p = 0.016). However, an age-related significant increase in minor flap complications could be observed in the elderly (p = 0.008). A significant correlation between minor medical complications and age could be observed (p = 0.001) in contrast to ASA score (p = 0.912).Conclusion An increased minor flap, as well as minor and major medical complications, must be expected in extremity reconstructions with free gracilis flaps in elderly patients. Higher ASA scores correlate with a higher incidence of major flap complications. Septuagenarians are more prone to develop perioperative major medical complications than patients younger than 70 years. Age and general medical condition, coupled with the performance of each patient, should be thoroughly assessed individually to facilitate a tailored reconstructive approach using risk assessment tools and established scoring systems.
Keywords: elderly; microsurgery; gracilis flap